2023
DOI: 10.7717/peerj.16401
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroquinolone resistance determinants in carbapenem-resistant Escherichia coli isolated from urine clinical samples in Thailand

Parichart Boueroy,
Peechanika Chopjitt,
Rujirat Hatrongjit
et al.

Abstract: Background Escherichia coli is the most common cause of urinary tract infections and has fluoroquinolone (FQ)-resistant strains, which are a worldwide concern. Objectives To characterize FQ-resistant determinants among 103 carbapenem-resistant E. coli (CREc) urinary isolates using WGS. Methods Antimicrobial susceptibility, biofilm formation, and short-read sequencing were applied to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Intriguingly, a third of patients with a resistant isolate did not have any documented risk factors for resistance [38]. Given that uropathogens endowed with specific virulence factors are also evidently surviving in hyperosmotic urine [17,18], it is likely that prior exposure to antibiotics give rise to microbial colonies with stimulated biochemical mechanisms that not only confers virulence but also predisposes to AMR [19,21] development.…”
Section: Contribution Of Urinary Tract Infections (Utis) To Amrmentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, a third of patients with a resistant isolate did not have any documented risk factors for resistance [38]. Given that uropathogens endowed with specific virulence factors are also evidently surviving in hyperosmotic urine [17,18], it is likely that prior exposure to antibiotics give rise to microbial colonies with stimulated biochemical mechanisms that not only confers virulence but also predisposes to AMR [19,21] development.…”
Section: Contribution Of Urinary Tract Infections (Utis) To Amrmentioning
confidence: 99%
“…Uropathogens exposed to below-MIC levels in urine bestow The infection of the urothelium can only occur after uropathogens successfully compete for available nutrients with the commensal microbiome [13] by employing mechanisms of commensalism [14], mutualism, and parasitism [15,16]. Many groups have suggested that the biochemical mechanisms driving the adaptability of uropathogens in the variable pH and osmolality of urine [17,18] are as dogged as the signaling pathways driving the gain of virulence [19][20][21] and antimicrobial resistance (AMR) [22]. From a clinical perspective, AMR refers to a microbial phenotype capable of surviving the exposure to a drug treatment course at a concentration anticipated to prevent its survival [20].…”
Section: Introductionmentioning
confidence: 99%
“…These findings highlight the urgency for efficient strategies and control policies to mitigate the spread of fluoroquinolone-resistant CREc strains, offering valuable insights for ongoing efforts in monitoring and combating antimicrobial resistance. [23] The resistance patterns among Enterobacteriaceae isolated from urinary tract infections (UTIs) exhibited High rates of quinolone resistance among ESBL-producing isolates highlighting the increasing challenge of antibiotic resistance in this clinical context. The identification of PMQR genes, notably aac(6′)-Ibcr, in a significant proportion of samples, adds complexity to the resistance landscape.…”
Section: Quinolone-resistance In Urinary Pathogensmentioning
confidence: 99%
“…ESBLs, typically encoded on plasmids, confer resistance to a broad spectrum of antibiotics, including most penicillins, cephalosporins, and aztreonam, through their enzymatic hydrolysis [2]. Additionally, while ESBLs do not directly deactivate non-beta-lactam agents, microorganisms carrying ESBLs often harbor genes that confer resistance to other antibiotics such as ciprofloxacin, gentamicin, or trimethoprim-sulfamethoxazole [3,4].…”
Section: Introductionmentioning
confidence: 99%